Is per capita fish consumption in Latin America aligned with international recommendations for a healthy diet? - GUZMÁN-PINCHEIRA, Carla; ANDRADE-CUVI, María José; PEREZ, Juan Carlos Bórquez; ARAUJO-SILVA, Gabriel; QUINTERO-FLÓREZ, Angélica (Food Science and Technology, 2024)
The World Health Organization (WHO) is urging Latin American countries to prioritize the prevention of chronic noncommunicable diseases. Diet is a crucial factor in determining one’s health, and healthy eating recommendations emphasize the consumption of fish at least twice a week due to its protein, vitamin, mineral, and essential fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). This review was designed to compare the status of fish consumption as a source of EPA and DHA fatty acids in some Latin American countries (namely Brazil, Chile, Colombia, and Ecuador), and comparisons with international recommendations within a healthy diet could contribute to the WHO’s call for a focus on preventing the aforementioned diseases in the region. A comprehensive literature search was conducted from January to October 2022 using PubMed, Scopus, EBSCO, and government compendia. Keywords included “fish,” “consumption,” “fatty acids,” “nutrients,” and “Latin America;” and “fish,” “chronic non-communicable diseases,” “all-cause mortality,” “obesity,” “cancer,” “neurodegenerative diseases,” “metabolic diseases,” “diabetes,” “polycystic ovary syndrome,” and “metabolic syndrome.” In countries such as Chile, Brazil, and Colombia, per capita fish consumption falls below WHO’s recommended levels, and the most commonly eaten species do not contain sufficient polyunsaturated fatty acids to provide an optimal intake of EPA and DHA. It is therefore recommended that each country review its dietary guidelines and fish recommendations based on the most commonly consumed species to ensure that their populations obtain the recommended intake of EPA and DHA fatty acids and thus the benefits related to the prevention of chronic noncommunicable diseases.